Immunogenic Potential of Beer Types Brewed With Hordeum and Triticum spp. Malt Disclosed by Proteomics - Spada, Valentina; Di Stasio, Luigia; Picascia, Stefania; Messina, Bernardo; Gianfrani, Carmen; Mamone, Gianfranco; Picariello, Gianluca (Frontiers in Nutrition, 2020)
The protein/peptide composition of five beer kinds, including two experimental beer-like products brewed with einkorn (Triticum monococcum), a beer labelled as “gluten-free”, a traditional all-barley malt and a wheat (T. aestivum) containing beer, was characterized with HPLC-ESI MS/MS-based proteomics. To enlarge the characterization of the components, the polypeptides were fractionated according to their molecular size (cut-off 6 kDa). All the beer types contained a variety of polypeptides arising from all the gliadin subfamilies (α-/β-, γ- and ω-gliadins) able to induce an immune response in celiac disease (CD) patients in addition to a panel of IgE-reactive food allergens. Wheat storage proteins were heavily hydrolyzed in the beer samples brewed with einkorn. The presence of gluten-like fragments, also including the 25-mer and 33-mer-like of α-gliadin, was confirmed in beer brewed with barley and wheat malt as well as in the gluten-free beer. Both CD-toxic and allergenic peptides of all beer samples were drastically degraded when subjected to a simulated gastroduodenal (GD) digestion. After in vitro digestion, the level of gluten-like peptides assayed with the G12 competitive ELISA, was below the threshold (20 ppm) for a food to be considered as “gluten-free”. A few gliadin-derived epitopes occurred in the digests of beers crafted with wheat or Norberto-ID331 line of einkorn. In contrast, digests of all barley malt and gluten-free beers did not contain detectable gluten-like epitopes, but only minor fragments of hordeins and IgE-reactive food allergens. All beer samples evoked a weak immune response on gliadin-reactive celiac T cells isolated from intestinal biopsies of celiac patients. Compared to undigested polypeptides, the response was markedly reduced by GD digestion. Although the consumption of a moderate amount of beer brewed with barley or einkorn could deliver a relatively low amount of CD-toxic epitopes, the findings of this study emphasize the urgent need of a reliable and accurate quantification of gluten epitopes in all types of beer, also including the gluten-free one, to compute realistically the contribution of beer to the overall gluten intake, which can be responsible of intestinal tissue damages in celiacs.